The TOPOGRAPHY MAP MAKING OF THE TAHFIDZ AL-QUDS BOARDING SCHOOL OF THE AR-RISALAH AL-ALAMIYAH RIAU - Eno Suwarno; yose Rizal; Fadrizal Lubis; Muhammad Ikhwan (Universitas Lancang Kuning, 2023)
The availability of topographical maps is indispensable for planning the physical development and landscape arrangement of the Tahfizh Al-Quds Islamic Boarding School. Currently for the manufacture of topographic maps can use drones. Partners do not yet have the skills to do this. The solution offered by the Lancang Kuning University service team is to assist in making topographic maps. Aerial photography is done by using a drone. Furthermore, the data is processed using the Agisoft Photoscan and ArcGIS applications. Based on the topographic map, there are 12 contour lines. The highest area is in the North Southwest, while the lowest area is on the outermost polygon line. Areas that are relatively sloping are in the West to the North, while areas that are steep are in the East to the Southeast. This map can be used as a guide for physical development and infrastructure according to the characteristics of the land.